Optimization of Ballast Water Management System on MV Sun Winner II to Ensure Operational Stability During Port Cargo Handling - Ababil, Alfin; Sutoyo, Sutoyo; Kusumawati, Elly; Haryanto, Tri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The stability of bulk carriers during high-rate cargo operations represents a critical intersection of naval architecture, mechanical engineering, and operational management. This study investigates the systemic inefficiencies in the ballast water management system of the MV Sun Winner II, a Supramax bulk carrier operating in the Indonesian archipelago, specifically analyzing the technical impediments encountered during cargo handling at Muara Berau port on February 14, 2024. Utilizing a descriptive qualitative methodology, data were acquired through direct shipboard observations, semi-structured interviews with senior deck officers, and rigorous documentation analysis over a 12-month sea service period. The research identifies a significant degradation in ballast performance attributed to sediment accumulation (sludge) exceeding 2 cm in tank bottoms, advanced corrosion of suction valves, and reduced centrifugal pump efficiency, which collectively resulted in a cargo intake shortfall of approximately 2,000 metric tons against a planned 23,000-ton capacity. The study reveals a critical dissonance between the administrative Planned Maintenance System (PMS) records and the physical reality of the vessel's ballast infrastructure, highlighting the "administrative-physical gap" as a latent risk factor. The findings suggest that on aging vessels (25+ years), standard maintenance protocols are insufficient; an enhanced regime of predictive maintenance, aggressive de-silting, and comprehensive valve overhauls is required to ensure compliance with SOLAS stability criteria and to maximize commercial voyage capability.